Terminal complement inhibition and control of hemolysis in patients with paroxysmal nocturnal hemoglobinuria who switched from high-dose eculizumab to ravulizumab: a phase IV, single-arm clinical trial - Morag Griffin; Shreyans Gandhi; Richard J. Kelly; Talha Munir; Roochi Trikha; Eden Hicks; Deepak Jain; Masayo Ogawa; Ji Yu; Petra Muus; Austin G. Kulasekararaj (Haematologica)
Not available.